Engineered nano-sphere array of gold-DNA core–shells and junctions as opto-plasmonic sensors for biodetection. Issue 44 (9th August 2021) - Osanloo, Nahid; Ahmadi, Vahid; Naser-Moghaddasi, Mohammad; Darabi, Elham
Abstract : Several engineered optoplasmonic structures including DNA rods as junctions between GNPs for controlling and improving the absorbance were proposed. Abstract : In this paper, we design opto-plasmonic sensors by the engineered arrangement of gold-nanospheres. We use DNA-gold nanoparticle (GNP) core–shells and DNA rods as junctions between GNPs with a fishnet ground layer for controlling and improving the absorbance and reflection in the range of 100–300 THz. Based on available data, we check the effects of healthy and cancerous cells on the reflection parameter. Here, we demonstrate how the DNA junctions and distance between the nanospheres can be considered to modify the reflection. These structures can be utilized as opto-plasmonic sensors with high sensitivity to distinguish materials in terms of refractive indices. We can use an array of these sensors for both spectroscopy and optical imaging on a real scale. The proposed structures with different topologies are analyzed and their figure of merits (FOM) and sensitivities are obtained. The structure based on the DNA rods as junctions between GNPs shows the best FOM value of 340 RIU −1 and the core–shell heptamer structure has the best sensitivity of about 1287 nm RIU −1 .